The Mediating Role of Intellectual Capital in the Relationship between Human Resource Management Practices and Enterprise Risk Management: Evidence from Egyptian Banks - Amin, Hend Medhat; EL-shawadfy, Mohamed Ghamry; Shahwan , Tamer Mohamed (Journal of Ecohumanism, 2024)
This paper aims to investigate the impact of intellectual capital (IC) as a mediator variable on the association between human resources management practices (HRM) practices and enterprise risk management (ERM) within the Egyptian banking sector. This study also examines bi-causality linkages between these variables, highlighting the dynamic interplay between these functions. The designated HRM practices index, the ERM index and the value-added intellectual coefficient method were used to assess the level of HRM practices, ERM maturity and the performance of IC, respectively. The content analysis approach, structural equation modeling (SEM) and Granger causality tests have been used to examine data collected from financial statement of the Egyptian banks listed in the Egyptian stock exchange. The data set is derived from 13 banks listed in the Egyptian exchange from 2018 to 2022. The findings revealed that HRM has a direct impact on enterprise risk management by ensuring that employees are well-trained, engaged, and motivated to adhere to risk protocols. Additionally, VAIC as a partial mediator enhances this relationship, allowing banks to utilize their intellectual resources—such as human skills, organizational structures, and capital—more effectively in risk management. Moreover, a bi-causality relationship can be observed between HRM practices and ERM.